Evaluating the impact of COVID-19 countermeasures on alcohol consumption through wastewater-based epidemiology: A case study in Belgium. (December 2022) - Boogaerts, Tim; Bertels, Xander; Pussig, Bram; Quireyns, Maarten; Toebosch, Louis; Van Wichelen, Natan; Dumitrascu, Catalina; Matheï, Catherina; Lahousse, Lies; Aertgeerts, Bert; De Loof, Hans; Covaci, Adrian; et al.
Graphical abstract: Highlights: Analysis of 735 daily influent wastewater samples for ethyl sulphate. Temporal changes in alcohol use during the COVID-19 pandemic. STL decomposition and dynamic regression with ARIMA errors used to assess time trends. Mobile phone data was applied as population proxy to measure population movements. Abstract: Wastewater-based epidemiology (WBE) is a complementary approach to monitor alcohol consumption in the general population. This method measures concentrations of xenobiotic biomarkers (e.g., ethyl sulphate) in influent wastewater (IWW) and converts these to population-normalized mass loads (PNML, in g/day/1000 inhabitants) by multiplying with the flow rate and dividing by the catchment population. The aims of this case study were to: (i) investigate temporal trends in alcohol use during the COVID-19 pandemic; and (ii) measure the effect of policy measures on alcohol consumption. Daily 24-h composite IWW samples (n = 735) were collected in the wastewater treatment plant of the university city of Leuven (Belgium) starting from September 2019 to September 2021. This is the first study that investigates alcohol use through WBE for a continuous period of two years on a daily basis. Mobile phone data was used to accurately capture population fluxes in the catchment area. Data was evaluated using a time series based statistical framework to graphically and quantitatively assess temporal differences in the measured PNML. Different WBE studies observed temporal changes in alcohol use during the COVID-19 pandemic. In this study, the PNML of ethyl sulphate decreased during the first lockdown phase, potentially indicating that less alcohol was consumed at the Leuven area during home confinement. Contrastingly, alcohol use increased after the re-opening of the catering industry. Additionally, a decrease in alcohol use was observed during the exam periods at the University of Leuven and an increase during the holiday periods. The present study shows the potential of WBE to rapidly assess the impact of some policy measures on alcohol consumption in Belgium. This study also indicates that WBE could be employed as a complementary data source to fill in some of the current knowledge gaps linked to lifestyle behavior.